Evaluation of Knowledge of Emergency Healthcare Workers Regarding Approach to Emergency Patients - Özgür Tanr›verdi; Oben Duman (Haseki Tıp Bülteni)
Aim: Emergency units constitute the most important part of all hospitals. The aim of this study was to evaluate practitioners’ and healthcare providers’ knowledge and experience regarding emergency first aid in a hospital with insufficient facilities. Methods: 17 physicians and 25 assistant staff working at our hospital were evaluated in terms of their knowledge about and experience in “emergency medicine and trauma” by a questionnaire and by observations. Results: The results of observations and questionnaire indicated that knowledge and experience among physicians were inadequate in terms of basic life support and advanced cardiac life support. This lack of knowledge was not associated with age, time of employment, faculty graduated and training on “emergency medicine” in the group of physicians (r=0.301 p>0.05, r=0.317 p>0.06, r=0.228 p>0.05, r=0.284 p>0.05, respectively) and in the group of assistant staff (r=0.341 p>0.05, r=0.287 p>0.06, r=0.234 p>0.05, r=0.227 p>0.05, respectively). Conclusion: Considering that the most of the physicians are gathered in certain regions of our country and that there is a lack of emergency medicine specialists in underdeveloped regions, it has been concluded that physicians specialized in other areas and practitioners must attend emergency medicine trainings under the concept of “emergency medicine rotation”. (The Medical Bulletin of Haseki 2010; 48:103-5)